Políticas de avaliação institucional da educação superior : criação e implementação do sistema de avaliação do ensino superior de Cabo Verde - Cardoso, António Pedro Barbosa (2017)
This research fits in the discussions and reflections on the Institutional Evaluation of Higher Education, focus on the implementation of the System of the Evaluating the Higher Education of Cabo Verde, which is a form of the Public Educational Policy, Institutionalized by the State of Cabo Verde, with the purpose of supervising, regulating and measuring the relevance and quality of the educational offerings of its Higher Education System, with technical and scientific advisory of the Brazilian State, by the INEP servers, under the South-South Cooperation between the two aforementioned Nations. It is problematic central: How the process of creating and implementing the System for Evaluating the Higher Education of Cabo Verde is developed, in the perspective of the subjects involved: Authorities of the Ministry of Higher Education Science and Innovation of Cabo Verde; Managers (Rectors) of the IES of Cabo Verde; International Consultants? One of the assumed assumptions is that the debility and the weaknesses of the State of Cape Verde can be overcome, if there is a strong bet in Higher Education, with a quality of excellence, which provides opportunities for schooling, as the main way of ascension and rising social mobility of its citizens. According, of the theoretical-epistemological orientation, is found in the critical research paradigm, specifically, in the South Epistemologies, made from an invocation perspective, of its heuristic potential, into as a gradient of analysis, which allows us to recognize some features attributable the themes developed in the Global South and locate in space and time, the place of the subject's enunciation. It was developed from the approach of Qualitative Research, with the support of the foundations of documentary research and state of knowledge. The empirical data was collected from the part-structured interview to 13 subjects, which are elites of Higher Education, from Cabo Verde, Portugal and Brazil. The analysis of the empirical data was made from the Approach of the Policy Cycle, embodied in its contexts of Influence, Text and Practice, which emerges from the perception of the subjects interviewed. As results, it is understood that the institutionalisation of the aforementioned System arises as a regulatory instrument, supervision, social control and accountability of educational offerings in Cabo Verde, from 2014 in a systematized and formalized manner, arising from approval and publication of legal instruments for this purpose. It is still evident, which is a process strongly influenced by the negotiation of the Higher Education authorities, with the elites of Institutions of the Country's Higher Education and international mediators. Ensure that the project initially planned for the creation of the aforementioned system was partially implemented, due to conflicts, tensions and interests, mainly of political nature, among the protagonists involved, notably the alternation of political power. Finally, it is noted that the aforementioned system, transitions between theoretical and epistemological influences of the Brazilian and European evaluation system, with the guidelines of the Bologna Convention, as main references, imposed by the necessity and relevance of the comparison of educational offers of Cabo Verde with international similar practices.